1990
DOI: 10.1152/ajpcell.1990.259.6.c933
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory influence of phosphate and arsenate on contraction of skinned skeletal and cardiac muscle

Abstract: It has been widely observed that Pi decreases maximum calcium-activated force (Fmax) and calcium sensitivity of skinned skeletal and cardiac muscle. However, whether a particular ionic species of Pi (i.e., H2PO4-) is responsible for these effects is controversial. To clarify this issue, we examined the influence of Pi and its structural analogue arsenate (Asi) on contraction of skinned rabbit psoas (fast twitch), soleus (slow twitch), and cardiac papillary muscle. Asi decreased Fmax of all three muscles types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
43
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 26 publications
20
43
1
Order By: Relevance
“…18 It has been shown that the effects of P i and pH on isometric force are independent in cardiac muscle. 2,13,19 Our results are in agreement with these studies because the product of the relative reductions in force by 30 mmol/L P i and pH 6.2 separately did not significantly differ from the combined effect found under simulated ischemic conditions (30 mmol/L P i , pH 6.2).…”
Section: Combined Effects Of P I and Phsupporting
confidence: 91%
“…18 It has been shown that the effects of P i and pH on isometric force are independent in cardiac muscle. 2,13,19 Our results are in agreement with these studies because the product of the relative reductions in force by 30 mmol/L P i and pH 6.2 separately did not significantly differ from the combined effect found under simulated ischemic conditions (30 mmol/L P i , pH 6.2).…”
Section: Combined Effects Of P I and Phsupporting
confidence: 91%
“…Interestingly, the contractile properties of cardiac muscle preparations appear to be more sensitive to added P i than those of skeletal muscle preparations. For instance, Nosek et al (29) reported that 10 mM added P i decreased cardiac muscle force ϳ60% compared with a 40% force decline in skeletal muscle preparations in the same study. We also observed that force declined ϳ65% in the cardiac myocyte preparation in response to 10 mM added P i .…”
Section: Discussionmentioning
confidence: 76%
“…There seems to be agreement that Pi reduces force by reducing the number of cross-bridges in high-force-producing states (Pate & Cooke, 1989;Dantzig et al 1992 (Nosek, Fender & Godt, 1987;Nosek, Leal-Cardoso, McLaughlin & Godt, 1990). However, others have failed to see synergism even in fast-twitch fibres (Chase & Kushmerick, 1988;Pate & Cooke, 1989).…”
Section: Reduction Of Maximum Isometric Forcementioning
confidence: 99%